Analisis Efektivitas E-Faktur Versi 3.0 Dalam Pelaporan Pajak Pertambahan Nilai Pada Kantor Pelayanan Pajak Pratama Jakarta Kebayoran Baru Satu Tahun 2020 - Gita Silvana Putria; Jiwa Pribadi Agustianto; Yopy Ratna Dewanti (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This study aims to discuss the effectiveness of E-Faktur Version 3.0 in Value Added Tax Reporting at KPP Pratama Jakarta Kebayoran Baru Satu. The main issue discussed in this study is how the level of effectiveness of the latest E-Faktur Version 3.0 in Value Added Tax Reporting. The research was conducted at KPP Pratama Jakarta Kebayoran Baru employing a descriptive approach and data collection technique using interviews and documentation where researchers calculated the effectiveness level of E-Faktur Version 3.0 in Value Added Tax Reporting. To find out the actual situation, I conducted interviews with several parties. Based on the results of the study, in 2020 the effectiveness level of EFaktur Version 3.0 has been said to be effective in helping to facilitate Taxpayers, but it cannot be said to be effective in solving Taxpayer reporting compliance issues. The contributing factors are the lack of awareness of taxpayers, lack of technology literacy of the Taxpayer, and lack of socialization from the KPP to PKP or taxpayersThis study aims to discuss the effectiveness of E-Faktur Version3.0 in Value Added Tax Reporting at KPP Pratama Jakarta Kebayoran Baru Satu. The main issue discussed in this study is how the level of effectiveness of the latest E-Faktur Version 3.0 in Value Added Tax Reporting. The research was conducted at KPP Pratama Jakarta Kebayoran Baru employing a descriptive approach and data collection technique using interviews and documentation where researchers calculated the effectiveness level of E-Faktur Version 3.0 in Value Added Tax Reporting. To find out the actual situation, I conducted interviews with several parties. Based on the results of the study, in 2020 the effectiveness level of EFaktur Version 3.0 has been said to be effective in helping to facilitate Taxpayers, but it cannot be said to be effective in solving Taxpayer reporting compliance issues. The contributing factors are the lack of awareness of taxpayers, lack of technology literacy of the Taxpayer, and lack of socialization from the KPP to PKP or taxpayers